(untitled) (A Text Book of Pharmaceutics for I Year Diploma in Pharmacy, 2024)
Author Dr. Basu Venkateswara Reddy Professor and Head, Department of Pharmaceutics, Sri.K.V.College of Pharmacy, Chikkaballapura, Karnataka, India Abstract: Novel Drug Delivery Systems (NDDS) represent advanced approaches to delivering pharmaceutical compounds in ways that enhance therapeutic efficacy, improve patient compliance, and reduce side effects. This section explores various innovative drug delivery technologies and their applications in modern pharmaceutical practice. Controlled release systems, including matrix tablets, reservoir devices, and osmotic systems, are examined for their ability to maintain therapeutic drug levels over extended periods. Targeted drug delivery approaches, such as nanoparticles, liposomes, and antibody-drug conjugates, are discussed in the context of improving drug specificity and reducing systemic toxicity. Transdermal delivery systems, including patches and iontophoretic devices, are explored for their potential in providing non-invasive, controlled drug administration. Pulmonary drug delivery systems, such as dry powder inhalers and metered-dose inhalers, are addressed, highlighting their importance in respiratory therapeutics. The principles of mucoadhesive drug delivery for improving gastrointestinal and nasal absorption are examined. Advanced technologies like 3D printing in pharmaceutical manufacturing and its potential for personalized medicine are briefly discussed. Challenges in developing NDDS, including formulation complexities, scale-up issues, and regulatory considerations, are addressed. Keywords: Controlled release, Targeted delivery, Nanocarriers, Transdermal systems, Personalized medicine, Smart therapeutics View PDF